Coastal fallout of settleable particulate matter: Metal bioaccumulation and sublethal toxicity in estuarine bivalves with implications for human health - Duarte, Luís Felipe de Almeida; Ortega, Andressa Dos Santos Barbosa [UNESP]; Paço, Marina de Souza; Nobre, Caio Rodrigues; Sadauskas-Henrique, Helen; Gusso-Choueri, Paloma Kachel; Souza, Iara Costa; Carvalho, Mariana V; Monferrán, Magdalena Victoria; Wunderlin, Daniel Alberto; Fernandes, Marisa Narciso; Pereira, Camilo Dias Seabra (Elsevier, 2025)
Settleable atmospheric particulate matter (SePM) from metallurgical sources can introduce toxic elements into coastal ecosystems, affecting aquatic biota and human health. This study evaluated the effects of SePM exposure (0.01, 0.1, and 1 g/L) on the estuarine oyster Crassostrea rhizophorae over 30 days, followed by a 30-day depuration. The concentrations reflect environmentally realistic scenarios based on particulate deposition and metal load data reported for industrial coastal regions such as Tubarão Port, southeastern Brazil. We analyzed metal bioaccumulation (29 elements) and sublethal responses using biomarkers of cytotoxicity (NRRT), genotoxicity (DNA strand breaks), lipid peroxidation (LPO), and acetylcholinesterase (ChE) activity. Human health risks were assessed for oysters exposed to SePM via Estimated Daily Intake (EDI) and Target Hazard Quotient (THQ). Eight elements (Al, V, Fe, Ni, Zn, As, Sr, Cd) accumulated significantly in exposed oysters. Cd and Fe were partially eliminated during depuration. Cytotoxicity and genotoxicity increased markedly, correlating positively with internal Ni, Fe, and V levels. In contrast, LPO and ChE showed no significant changes. Despite significant bioaccumulation, all EDI and THQ values remained below USEPA safety thresholds, indicating no immediate risk to human consumers following a 30-day exposure. This is the first study to jointly evaluate ecotoxicological responses and human health risks in a native estuarine bivalve exposed to SePM, integrating environmental monitoring with food safety within a One Health perspective. Our findings highlight ecological vulnerability and underscore the need for long-term assessments of particulate pollution in seafood species. Future longitudinal studies are recommended to assess the effects of extended dietary exposure and metal persistence in bivalve tissues under natural estuarine conditions.